EKSTRAKSI GELATIN DARI TULANG IKAN KAKAP PUTIH (Lates calcarifer) DENGAN VARIASI KONSENTRASI ASAM HCl - Bhayu Gita Bhernama (JURNAL SAINS NATURAL, 2020)
Extraction of Gelatin from Fish White Bone (Lates Calcarifer) with HCl Concentration VarianceÂ Gelatin is a food added ingredient used in emulsifiers, thickeners, food stabilizers. Gelatin is a type of protein in the form of gel obtained from the denaturation of skin, bone and fish tissue collagen denaturation. The process of making gelatin from the bones of white snapper (Lates calcarifer) uses the HCl acid method with the parameters of yield, water content, ash content, and protein content. The immersion process carried out with varoius of HCl acid concentration 3%, 7% and 11%.The results show that the best value of% yield at a concentration of 7% of 1.90%, 10.16% water content. Ash content 3%. Protein content is 3.25%. FTIR spectrum revealed the presence of amida group at wave number 3269 cm-1, amide I; II; and Amida III sequentially at wave number 1656 cm-1; 1525.69 cm-1; 1161.15 cm-1.Keywords : Gelatin ; collagen ; Lates calcarifer ; FTIRABSTRAKÂ Gelatin merupakan bahan tambah pangan yang digunakan dalam pengemulsi, pengental, penstabil makanan. Gelatin merupakan salah satu jenis protein yang berbentuk gel yang didapatkan dari hasil denaturasi kolagen kulit, tulang dan jaringan ikan. Proses ekstrak gelatin dari bahan tulang ikan kakap putih (Lates calcarifer) menggunakan asam HCl dengan parameter rendemen, kadar air, kadar abu, kadar protein dan analisis FTIR. Proses perendaman dilakukan variasi asam HCl 3%, 7% dan 11%. Dari hasil penelitian didapatkan nilai % rendemen tertinggi pada konsentrasi 7% sebesar 1,90%, dengan nilai kadar air 10,16%, kadar abu 3,00%, kadar protein 3,25%. Dari spektrum FTIR didapatkan gugus Amida A pada bilangan gelombang 3269 cm-1, amida I ; II ; dan amida III secara berturut-turut pada bilangan gelombang 1656 cm-1 ; 1525,69 cm-1 ; 1161,15 cm-1.Kata kunci : Gelatin ; ikan kakap putih ; FTIR